2013
DOI: 10.1073/pnas.1312956110
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope homogeneity of oceanic DMSP and DMS

Abstract: Oceanic emissions of volatile dimethyl sulfide (DMS) represent the largest natural source of biogenic sulfur to the global atmosphere, where it mediates aerosol dynamics. To constrain the contribution of oceanic DMS to aerosols we established the sulfur isotope ratios ( 34 S/ 32 S ratio, δ 34 S) of DMS and its precursor, dimethylsulfoniopropionate (DMSP), in a range of marine environments. In view of the low oceanic concentrations of DMS/P, we applied a unique method for the analysis of δ 34 S at the picomole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 30 publications
14
78
1
Order By: Relevance
“…Indeed, the existing data sets include one from the South Pole covering approximately the past 50 years [ Patris et al ., ], the Camp Maudheimvidda (CM) and Camp Victoria (CV) ice cores from Dronning Maud Land (spanning the present to 1100 years ago) [ Jonsell et al ., ], and the Dome C shallow core [ Baroni et al ., ] (Figure ). These East Antarctic sites have δ 34 S values ranging from 13.9 to 18.1‰, similar to biogenic sulfur [ Amrani et al ., ; Calhoun et al ., ; Oduro et al ., ], suggesting that marine biogenic activity has a strong influence in East Antarctica. The contributions of other sources to the total sulfate are estimated to be minor: Volcanic degassing is estimated to contribute 10–20% based on a δ 34 S value from CV [ Jonsell et al ., ], and stratospheric sulfate is estimated to contribute approximately 5% based on aerosol chemistry observations at Neumayer Station [ Minikin et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the existing data sets include one from the South Pole covering approximately the past 50 years [ Patris et al ., ], the Camp Maudheimvidda (CM) and Camp Victoria (CV) ice cores from Dronning Maud Land (spanning the present to 1100 years ago) [ Jonsell et al ., ], and the Dome C shallow core [ Baroni et al ., ] (Figure ). These East Antarctic sites have δ 34 S values ranging from 13.9 to 18.1‰, similar to biogenic sulfur [ Amrani et al ., ; Calhoun et al ., ; Oduro et al ., ], suggesting that marine biogenic activity has a strong influence in East Antarctica. The contributions of other sources to the total sulfate are estimated to be minor: Volcanic degassing is estimated to contribute 10–20% based on a δ 34 S value from CV [ Jonsell et al ., ], and stratospheric sulfate is estimated to contribute approximately 5% based on aerosol chemistry observations at Neumayer Station [ Minikin et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report containing S isotopic information on Indian aerosols. Nonetheless, from available literature containing S isotopic composition data from other regions and oceanic realms (Norman et al, 1999;Oduro et al, 2012;Amrani et al, 2013), we showed typical end member values in the Fig. 6 and attempted to provide interpretation for observed δ 34 S values of bulk aerosols over Goa.…”
mentioning
confidence: 94%
“…As Goa is a typical costal locale experiencing strong biogeochemical in the coastal waters just before arrival of monsoon, enhancement of δ 34 S shows most likely tracks changes in the sulfur inventory. Recently Amrani et al (2013) and Oduro et al (2012) have shown oceanic emissions of volatile dimethyl sulfide (DMS) and its precursor, dimethylsulfoniopropionate (DMSP) represent the largest natural source of biogenic sulfur to the global atmosphere, where it mediates aerosol dynamics and may, in turn, affect climate. Amrani et al (2013) reported δ 34 S of DMS and DMSP ranging between +18.9 and +20.3‰, remarkable consistent across the globe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased continental biogenic emissions would tend to decrease the δ 34 S‐SO 4 2− values of summer rain, which is opposite to the trend observed in this study. However, sulfate derived from marine biogenic emissions (mainly dimethyl sulfide (DMS)) are substantial (~19% of annual global S emissions), with more positive δ 34 S‐SO 4 2− values (+18.9 to +20.3‰) [ Amrani et al, ; Seguin et al, ] relative to this study. Primary productivity from phytoplankton and algae that produce DMS is elevated in the summer [e.g., Li et al, ; Norman et al, ].…”
Section: Discussionmentioning
confidence: 90%